Reseña del libro “Ceramics and Society. A technological approach to archaeological assemblages” de Valentine Roux - Mary Ownby; Isabelle Druc (Anuario de Arqueología, 2022)
Reseña de libro: Ceramics and Society. A Technological Approach to Archaeological Assemblages (Springer, Switzerland, año 2019), de la autora Valentine Roux en colaboración con Marie-Agnès Courty.